Systematic review of the effect of reflective materials around a phototheraphy unit on biirubin reduction among neonates with physiologic jaundice in developing countries - Lee, Wan Fei S.; Chew, K.S.; Pawi S.; Chong, Li Tsu; Abdullah K.L.; Lim, L.T.; Rintika F. (Elsevier B.V., 2018)
Objective: To identify the efficacy and safety of the use of various cost-effective reflective materials around phototherapy units to reduce the duration of phototherapy and hasten the reduction of bilirubin among neonates with physiologic jaundice. Data Sources: A systematic review of randomized controlled trials identified from searches in the Cumulative Index to Nursing and Allied Health Literature, Science Direct, Embase, and the Cochrane Library with the use of keywords, MeSH terms, operators, and the review of reference lists of retrieved articles. Study Selection: From a total of 186 studies initially screened, five were eventually included in this analysis.